2021
DOI: 10.1002/edm2.277
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes among patients with chronic kidney disease hospitalized with diabetic foot disorders: A nationwide retrospective study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…29 Hypertension caused by renal insufficiency may lead to endothelial dysfunction, worsening of the lower limb ischemia, which harms the process of wound healing. 29 Several studies 19,21,30,31 revealed that renal insufficiency (eGFR <60 mL/min/1.73 m 2 ) was a risk factor for amputation in DFU patients. Our study confirms that severe reduced eGFR is associated with amputation risk after adjusting the confounders, including the PAD and infection degree (OR = 4.50, P = .03).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29 Hypertension caused by renal insufficiency may lead to endothelial dysfunction, worsening of the lower limb ischemia, which harms the process of wound healing. 29 Several studies 19,21,30,31 revealed that renal insufficiency (eGFR <60 mL/min/1.73 m 2 ) was a risk factor for amputation in DFU patients. Our study confirms that severe reduced eGFR is associated with amputation risk after adjusting the confounders, including the PAD and infection degree (OR = 4.50, P = .03).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have revealed that DFU patients may have adverse outcomes when combined with renal insufficiency, especially in patients with severe renal dysfunction or dialysis. 19 , 20 , 21 A retrospective study 22 about the long‐term diabetic complications as predictors of foot ulcers healing failure revealed that eGFR <60 mL/min/1.73 m 2 was an independent risk factor for poor wound healing. However, among patients with DFUs, patients with DFO are more complicated and worse prognosis than those without osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, severe amputations occurred in 31.98% of cases in the first year and 34.01% between the second and fifth years [5]. Patients entering the dialysis stage, whether hemodialysis or peritoneal dialysis, face a risk of DFU that is more than four times higher [6], and the incidence of amputation and sepsis will be more frequent, and the hospital stay will be longer [7]. The survival rate of DFU maintained dialysis patients was significantly lower than that of patients without foot ulcers [8].…”
Section: Introductionmentioning
confidence: 99%